Prime and Maximal Spectra of Almost Distributive Lattices and 0 - Distributive Lattices - Khopade, S. S.; Thorat, S. P. (Journal of Scientific Research, 2025)
The present research work attempts to bring together the two different algebraic structures namely almost distributive lattice (ADL) and 0-distributive lattice with the help of a special mapping which leads us to significant results. A surjection from an ADL with the least element and maximal element to a bounded 0-distributive lattice satisfying certain conditions is defined and studied. It is proved that this mapping induces a homeomorphism between their prime and maximal spectra.